Understanding Sophia?: On human interaction with artificial agents - Fuchs, Thomas (Phenomenology and the cognitive sciences, 2024)
Advances in artificial intelligence (AI) create an increasing similarity between the performance of AI systems or AI-based robots and human communication. They raise the questions: